Pentingnya Terapi Psikoreligi pada Lansia di Kelurahan Legok Kota Jambi - vevi suryenti putri; Nurhidayah Nurhidayah; Marnila Yesni; Ratu Kusuma (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Psychological comfort for the elderly, increasing the number of years and the higher life expectancy is a picture of the better quality of physical health, but we often forget the quality of mental health. The mental health of the elderly needs to be improved by one way of providing psychoreligious therapy. This therapy consists of four treatment sessions: the first session of anger control, the second session of anger control prayer, the third session of remembrance, the fourth session with positive action and thinking. This therapy is given in the form of community service activities in Legok Village, Jambi City in December 2021. Legok Village is one of the Stikes Baiturrahim Jambi target areas, where there is a fairly high elderly data from the total population. The number of elderly in Legok Village ranks second highest of all ages, namely 32%, adult age ranks first at 41% of the total population. RT 40 is one of the RTs in the Legok village with the most elderly data. The results of this service benefit the elderly who are in RT 40 Legok Village about psychological comfort and can improve mental quality. It can be seen from the results of the pre test and post test that there was an increase in knowledge about psychoreligious therapy in the elderly with an average of 1.9. With this increase in knowledge, the elderly can control negative thoughts into positive thoughts.